The effect of spray Silver Nanoparticles (Nivasha ) on Intensity of Cesarean Wound Pain; A Randomized Clinical Trial - Zakiyeh Boroumand; Nahid Golmakani; Seyed Reza Mazloum; Salmeh Dadgar; Shiva Golmohamadzadeh (Mashhad University of Medical Sciences, 2018)
Introduction: Cesarean section is one of the most common gynecological surgeries and pain is one of the most common problems after that. The silver nanoparticles with anti-inflammatory mechanism may be useful in reducing pain. Therefore, this study was performed with aim to determine the effect of silver nanoparticles (Nivasha ) spray on the intensity of cesarean wound pain. Methods: This triple-blind randomized controlled clinical trial was performed on 92 women with cesarean section in Mashhad Omolbanin educational hospital in 2017. Research units were randomly assigned in 3 groups. In two groups, Nyvasha and placebo spray was used on the caesarian wound twice a day for 10 consecutive days and each time 3 puffs; the control group didn't receive any drug. The intensity of pain was measured 20-28 hours after cesarean section and on the 5th and 10th days after it by Visual Analogue Scale. Data was analyzed by SPSS software (version 16) and Chi-square test and Kruskal Wallis test. P ˂ 0.05 was considered statistically significant. Results: After the intervention, the mean of pain intensity on day 5 in the silver nanoparticles, placebo, and control groups were 2.2 ± 1.1, 4.8 ± 1.3, 4.7±1.3 and on day 10 in the silver nanoparticles, placebo and control groups were 0.1 ± 0.4, 2.4 ± 1.5 and 2.0 ± 1.6, respectively. There was statistically significant difference in the pain intensity reduction in the silver nanoparticles group compared to the other two groups (P<0.001), however there was no significant difference between placebo and control group on day 5 (P = 0.84) and on day 10 (P = 0.37). Conclusion: Regarding the decrease in the intensity of cesarean section pain after the intervention, spray silver nanoparticles (Nivasha) is recommended as a suitable drug for reducing post-cesarean section pain in mothers.